Building adaptation - Douglas, James (Amsterdam ; Boston ; London : Butterworth-Heinemann, 2006)
"Building Adaptation is intended as a primer on the physical changes that properties can undergo during their service life. It is also a practical guide covering the general principles, techniques and processes involved in the alteration, conversion, extension, improvement and refurbishment of existing buildings. Numerous illustrations and examples are included that focus on a wide variety of different building types. Professional building surveyors, architects, construction managers and engineers should find this a welcome addition to their library and it is essential reading for degree and diploma students of these disciplines."-- BOOK JACKET.
Introduction -- Feasibility -- Principles of converting buildings -- Adaptive reuses -- Lateral extensions -- Vertical extensions -- Structural alterations -- Principles of refurbishment -- Further aspects of refurbishment -- Sustainable adaptation -- Implementation.
Includes bibliographical references (p. [595]-641) and index.
Keywords: Buildings -- Remodeling for other use; Buildings -- Repair and reconstruction